2013
DOI: 10.1007/s11250-013-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Body live weight and milk production parameters in the Majorera and Palmera goat breeds from the Canary Islands: influence of weight loss

Abstract: Seasonal weight loss (SWL), caused by poor quality pastures during the dry season, is the major limitation to animal production in the tropics. One of the ways to counter this problem is to breed animals that show tolerance to SWL. The objective of this study was to understand the effect of feed restriction in milk production and live weight (LW) evolution in two goat breeds, with different levels of adaptation to nutritional stress: the Majorera (considered to be tolerant) and the Palmera (considered to be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 20 publications
9
61
1
Order By: Relevance
“…It has an important impact on animal production systems in these areas, as supplementary feed is often necessary if not indispensable to prevent loss of production (Almeida et al, 2013). This phenomenon has been studied in goat bucks (Almeida, Schwalbach, Waal, Greyling, & Cardoso, 2006), sheep (Almeida et al, 2013, 2016; Ferreira et al, 2017; Miller et al, 2019; Ribeiro, Madeira, et al, 2019; Scanlon et al, 2013) and dairy goats (Hernández‐Castellano et al, 2016; Lérias et al, 2013, 2015; Palma, Hernández‐Castellano, et al, 2016). Specifically, Scanlon et al (2013) have reported sheep performance of Australian Merino, Damara and Dorper lambs.…”
Section: Introductionmentioning
confidence: 99%
“…It has an important impact on animal production systems in these areas, as supplementary feed is often necessary if not indispensable to prevent loss of production (Almeida et al, 2013). This phenomenon has been studied in goat bucks (Almeida, Schwalbach, Waal, Greyling, & Cardoso, 2006), sheep (Almeida et al, 2013, 2016; Ferreira et al, 2017; Miller et al, 2019; Ribeiro, Madeira, et al, 2019; Scanlon et al, 2013) and dairy goats (Hernández‐Castellano et al, 2016; Lérias et al, 2013, 2015; Palma, Hernández‐Castellano, et al, 2016). Specifically, Scanlon et al (2013) have reported sheep performance of Australian Merino, Damara and Dorper lambs.…”
Section: Introductionmentioning
confidence: 99%
“…Animal production in the tropics and the Mediterranean is strongly affected by pasture scarcity and quality during the dry summer and autumn months, leading to Seasonal Weight Loss (SWL), as we have demonstrated in South Africa34, Western Africa56, Western Australia7 and the Canary Islands89. To counter the effects of SWL, farmers use supplementation to balance the nutritional needs of the animals.…”
mentioning
confidence: 99%
“…To counter the effects of SWL, farmers use supplementation to balance the nutritional needs of the animals. Supplementation is expensive and difficult to implement in extensive production systems in developing countries or remote locations8. An alternative method for addressing the effects of SWL is the use of sheep breeds that are naturally adapted to this constraint and are able to thrive and more effectively produce in such difficult environments.…”
mentioning
confidence: 99%
“…The dietary concentrate level and nature of specific concentrate and forage feedstuffs impact level of milk production and characteristics of milk and milk products [31]. Nutrition affects both the yield and composition of the milk produced [32][33][34]. Energy is one of the limiting factors to high milk production.…”
Section: Effects Of Nutrition On Yield and Milk Composition In Goatsmentioning
confidence: 99%